Reliability of Hip Examination Tests for Femoroacetabular Impingement. Issue 10 (24th September 2013) - Ratzlaff, Charles; Simatovic, Jacqueline; Wong, Hubert; Li, Linda; Ezzat, Allison; Langford, Dolores; Esdaile, John M.; Kennedy, Carol; Embley, Patrick; Caves, Darryl; Hopkins, Trish; Cibere, Jolanda
<x xml:space="preserve">Abstract</x> Objective To assess the interrater reliability of hip examination tests used to assess femoroacetabular impingement (FAI) among clinicians from different disciplines. Methods Twelve subjects were examined by 9 clinicians using 12 hip tests drawn from a review of the literature and consultation with experts in hip pain and FAI. Examiners assessed both hips of each subject and were blinded to subject history. The order in which subjects were seen, the order of tests, and order of examination of the 2 hips within each subject were all randomized. Interrater reliability (IRR) for the 10 categorical tests was summarized using overall raw agreement (ORA), positive agreement (agreement on abnormal findings), and negative agreement (agreement on normal findings). An ORA of >0.75 was considered to indicate adequate reliability. For the 2 range of motion (ROM) outcomes, IRR was summarized using the median of the absolute difference (MAD) in measurements obtained by any 2 examiners on any patient. MAD reflects the "typical" difference (in degrees) between 2 raters. Results Adequate reliability (ORA >0.75) was achieved for 6 of the 10 hip examination tests with categorical outcomes. Positive agreement ranged from 0.35 to 0.84, while negative agreement ranged from 0.62 to 0.99. For the ROM outcomes, examiners were, on average, within 5° of each other for flexion and 7° for internal rotation. Conclusion The results provide evidence that the most common hip examination tests would likely be sufficiently reliable to allow agreement between examiners when discriminating between painful FAI and normal hips in a clinical setting.